Exploring Chemical Bonds through Variations in Magnetic Shielding - Karadakov, P.B.; Horner, K.E. (Journal of Chemical Theory and Computation, 2016)
Differences in nuclear isotropic magnetic shieldings give rise to the chemical shifts measured in NMR experiments. In contrast to existing NMR experimental techniques, quantum chemical methods are capable of calculating isotropic magnetic shieldings not just at nuclei, but also at any point in the space surrounding a molecule. Using s-trans-1,3-butadiene, ethane, ethene, and ethyne as examples, we show that the variations in isotropic magnetic shielding around a molecule, represented as isosurfaces and contour plots, provide an unexpectedly clear picture of chemical bonding, which is much more detailed than the traditional description in terms of the total electron density.
EPrint Processing Status: Full text deposited in DRO